2022
DOI: 10.3354/meps14193
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effectiveness of DNA barcoding for exploring hidden genetic diversity in deep-sea fishes

Abstract: The numbers of deep-sea fish species and their genetic diversities are poorly understood because of taxonomic confusion and the lack of robust diagnostic features. However, DNA barcoding using mitochondrial DNA sequences may offer an effective approach to identifying cryptic species and characterizing their genetic diversities. To validate the genetic differentiation identified by DNA mitochondrial barcoding, it is necessary to show that these reflect variations present in nuclear genomic markers. Here, we per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…variation and expand the geographic representation for this marker on GenBank. COI barcodes provided validation for our species identification and will also add to knowledge on intraspecific variation and geographic differentiation, which can facilitate the discovery of cryptic species (Kenchington et al, 2017;Teramura et al, 2022). Importantly, because we barcoded both the COI and 12S markers from the same specimens, we were able to detect species identification discrepancies on GenBank.…”
Section: Dna Barcoding and Reference Librarymentioning
confidence: 96%
See 1 more Smart Citation
“…variation and expand the geographic representation for this marker on GenBank. COI barcodes provided validation for our species identification and will also add to knowledge on intraspecific variation and geographic differentiation, which can facilitate the discovery of cryptic species (Kenchington et al, 2017;Teramura et al, 2022). Importantly, because we barcoded both the COI and 12S markers from the same specimens, we were able to detect species identification discrepancies on GenBank.…”
Section: Dna Barcoding and Reference Librarymentioning
confidence: 96%
“…DNA sequences were blasted against the GenBank database for comparison with publicly available sequences. Matches with 98% identity or greater for at least 90% of the read length were considered species-level identifications (e.g., Kenchington et al, 2017;Teramura et al, 2022). Barcode identifications were compared with morphological identifications.…”
Section: Introductionmentioning
confidence: 99%
“…DNA barcoding using mitochondrial DNA sequences may offer an effective approach to identifying cryptic species and characterizing genetic diversities of deep-sea fish species [39]. DNA barcoding of mesopelagic and demersal fish collected around Japan and southern Taiwan.…”
Section: Cryptic Speciesmentioning
confidence: 99%
“…The additive effects of high habitat heterogeneity, on both small and large scales, are known to contribute to a highly diverse deep‐sea fauna (Paulus, 2021). Indeed, current systematics has shown that many meso‐ and bathypelagic fishes with a worldwide distribution have highly divided population structures or include several cryptic species (de Carlos et al, 2020; Teramura et al, 2022).…”
Section: Introductionmentioning
confidence: 99%